Comparison of Endoscopic Dacryocystorhinostomy (DCR) with and without Bodkin Tube (Silicon Tube) at MTI KTH Peshawar Ophthalmology and ENT Department - Bilal Khan, Azhar Farooq, Muhammad Haris Zia, Muhammad Usman, Suleman Khan, Ayyaz Hussain Awan, Imran Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: An effective surgical technique for saccal and postsaccal stenosis or nasolacrimal duct occlusion is endoscopic dacryocystorhinostomy (DCR). Endoscopic DCR with a silicone tube is contentious even now. Objective: The goal of this research was to determine if endoscopic DCR with or without a silicone stent was more effective. Methods: Total 20 patients underwent for endoscopic DCR were presented in this study. After getting informed written consent detailed demographics were recorded. Patients were equally divided in two groups. Group I received endoscopic DCR with silicon tube in 10 cases and 10 cases of group II went for endoscopic DCR without tube. Post-operatively outcomes were compared among both groups. Results: There were 13 (65%) females and 7 (35%) males among all cases. Mean age of the cases was 49.8 years. Left side was the most common found among all cases. Mean operative time in group I was lower as compared to group II with p value <0.004. We found 90% success rate in group I and 80% success in group II with insignificant difference. Frequency of recurrent watering in group I was lower as compared to group II with p value < 0.002. Conclusion: Results showed no statistically significant benefit to endoscopic DCR with stent compared to endoscopic DCR without stent in this study. Keywords: endoscopic DCR, silicon tube, success rate, recurrence